Experimental and Theoretical Studies on the Structure and Photoluminescent Properties of New Mononuclear and Homodinuclear Europium(III) β-Diketonate Complexes - João P. Martins; Pablo Martín-Ramos; Pedro Chamorro-Posada; Pedro S. Pereira Silva; Jesús Martín-Gil; Salvador Hernández-Navarro; Manuela Ramos Silva (Advances in Condensed Matter Physics)
Two novel europium(III) complexes, a monomer and a homodimer, with 1-(4-chlorophenyl)-4,4,4-trifluoro-1,3-butanedione (Hcbtfa) and 5-chloro-1,10-phenanthroline (cphen) ligands, formulated as [Eu(cbtfa)3(cphen)] and [Eu2(cbtfa)4(cphen)2(CH3O)2], have been synthesized. Their structures have been elucidated by X-ray diffraction and their absorption and emission properties have been studied in the solid state. The experimental data has then been used to test the recently released LUMPAC software, a promising tool which can facilitate the design of more efficient lanthanide light-conversion molecular devices by combining ground state geometry, excited state energy, and luminescent properties calculations.